PENGARUH LINGKUNGAN SOSIAL DAN MOTIVASI TERHADAP HASIL BELAJAR IPS SISWA SD INPRES PERUMNAS ANTANG KECAMATAN MANGGALA KOTA MAKASSAR - Perawati Bte Abustang (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2018)
This research aimed to know the impact of social environment against achievement of social science at students of SD Inpres Perumnas Antang of Manggala subdistrict of Makassar. Type of research was ex post facto using quantitative research. This research was conducted at SD Inpres Perumnas Antang of Manggala subdistrict of Makassar. Instrument of research was questionnaire to obtain variable data about social environment. Analysis data techniques were descriptive and inferential analyses by using SPSS version 20.0 for windows. Based on descriptive analysis, parents (mother and father) had moderate education level (senior high school) and parents’ jobs were mostly entrepreneur (father) and housewife (mother). Inferential analysis showed that sig.0.000 < α =0.05, H0 was rejected and H1 was accepted. Therefore, there was impact of social environment against achievement of social science at students of SD Inpres Perumnas Antang of Manggala subdistrict of Makassar. It can be concluded that there is impact of impact of social environment against achievement of social science at students of SD Inpres Perumnas Antang of Manggala subdistrict of Makassar.